Modification of the Asthenic State Assessment Scale - САВЧЕНКО, Олена; ДВОРЯКОВСЬКА, Тата (Київський національний університет імені Тараса Шевченка, 2025)
Background. Against the backdrop of chronic stress, manifestations of asthenic syndrome are becoming more widespread among Ukrainians. The issue of developing reliable means of psychological assessment of this condition has become acute. Methods. The article presents the results of the Ukrainian-language modification of the Asthenic State Scale (ASS-15) questionnaire. The main psychometric characteristics are determined. Results. Empirical research has shown that some of the questions in the unadapted Ukrainian-language version of the scale demonstrate low reliability and validity, which calls into question its accuracy and diagnostic value. Based on the results of factor analysis, additional subscales were identified that reflect various aspects/domains of asthenic syndrome. Based on the data obtained, the structure of the questionnaire was optimised: questions that showed low reliability and validity were removed. The results of confirmatory factor analysis showed the relevance of implementing a three-component model (X2 = 110, p = 0.05; CFI = 0.961; TLI = 0.953; RMSEA = 0.047, [0.02-0.07]). The updated version of the methodology is more compact, has sufficiently high internal consistency indicators (Cronbach's alpha from 0.70 to 0.83), allows for a differentiated assessment of individual components of asthenic state, and can be recommended for use in clinical, psychological, and scientific research. Conclusions. The article provides justification for the reduction and modification of the Asthenic State Scale and describes the procedure for distinguishing three subscales: cognitive, emotional, and physiological manifestations of asthenia.

Вступ. На тлі хронічного стресу в українців поширюються прояви астенічного синдрому. Гостро постає питання розробки надійних засобів психологічної оцінки стану. Методи. У статті представлено результати україномовної модифікації опитувальника «Шкала астенічного стану (ШАС-15)». Визначені основні психометричні характеристики. Результати. У ході емпіричного дослідження було виявлено, що частина питань неадаптованої україномовної версії шкали демонструє низькі показники надійності та валідності, що ставить під сумнів її точність і діагностичну цінність. За результатами факторного аналізу ідентифіковано додаткові субшкали, що відображають різні аспекти/домени астенічного синдрому. На основі отриманих даних було оптимізовано структуру опитувальника: вилучено питання, що показали низьку надійність та валідність. Результати конфірматорного факторного аналізу показали доречність впровадження трикомпонентної моделі (Х2 =110, р=0,05; CFI =0,961; TLI =0,953; RMSEA = 0,047, [0,02-0,07]). Оновлена версія методики є більш компактною, має достатньо високі показники внутрішньої узгодженості (альфа Кронбаха від 0,70 до 0,83), дозволяє диференційовано оцінювати окремі компоненти астенічного стану та може бути рекомендована для використання у клінічних, психологічних і наукових дослідженнях. Висновки. У статті наведено обґрунтування скорочення та модифікації «Шкали астенічного стану», наведений опис процедури виокремлення трьох субшкал: когнітивні, емоційні та фізіологічні прояви астенії.
Модифікація шкали оцінки астенічного стану
Keywords: asthenia; chronic fatigue syndrome; asthenic syndrome; Asthenic State Scale; cognitive manifestations; emotional manifestations; physiological manifestations; psychometric characteristics; астенія; синдром хронічної втоми; астенічний синдром; шкала астенічного стану; когнітивні прояви; емоційні прояви; фізіологічні прояви; психометричні характеристики